Habituasi Baru Tradisi Sedekah Bumi Pada Masa Pandemi dan Pasca Covid-19 di Punden Kelurahan Putat Gede Kota Surabaya: English, Indonesian - Maudiningrum, Aulia Ayu; Fauzi, Agus Machfud (Paradigma, 2023)
Abstract The Sedekah Bumi Ceremony is one of the traditions that has been passed down from generation to generation which is still carried out by the putat gede people from year to year. The Sedekah Bumi Ritual Ceremony is a tradition to avert evil and a form of gratitude for abundant sustenance. This study aims to identifiy The Sedekah Bumi Ritual Ceremony traditions that are still maintained by the community today, identify new habituation that exist in the implementation of the sedekah bumi ritual ceremony traditions during the pandemic and post-pandemic Covid-19, analyze the Sedekah Bumi Riutal Ceremony procession during the pandemic and post-pandemic Covid-19, as well as identifying symbolic instument in the sedekah Bumi Ritual Ceremony traditions This study uses a qualitative method with an ethnomethodological approach. The data in the research were obtained through interviews, observation and documentation. The theory used is that of Pierre Bourdieu’s habitus. The results of the study show that there is Covid-19 delayed the process of sedekah bumi Ritual Ceremony in Putat Gede. The traditional procession was stopped in the first year of the pandemic, after which it was held again in the second year. This traditional procession in the midst of the Covid-19 pandemic has led to a new habituation in its implementation. The procession that is carried out is only the main part and which is considered to have sacred value. Besides that, the village administration also only allows this tradition to be carried out for a few hours with very strict health protocols. the Sedekah Bumi Ritual Ceremony tradition was carried out again as before during the post pandemic period. This is indicated by the lifting of restrictions on crowd activities. Key Word: New Habituation ; The Sedekah Bumi Ritual Ceremony ; Simbolic